FRI0332 EVALUATION OF THE INDIVIDUAL COMPONENTS OF ACR50+PASI100 AND MDA AT WEEK 24 FROM THE SPIRIT-H2H TRIAL COMPARING THE EFFICACY AND SAFETY OF IXE VERSUS ADA IN PATIENTS WITH PSA NAÏVE TO BDMARDS. (2nd June 2020) - Coates, L. C.; Nissen, M.; El Baou, C.; Zochling, J.; Marchesoni, A.; Liu Leage, S.; Soriano, E.; Azevedo, V. F.; Machold, K.; Sapin, C.
Abstract : Background: Psoriatic arthritis (PsA) is a chronic systemic disease with manifestations affecting musculoskeletal and extra-articular domains. Treatment and assessment of response are therefore major challenges in routine clinical practice. Minimal disease activity (MDA) is a multidimensional endpoint that can define a treatment target 1 . In SPIRIT-H2H 2, a head-to-head clinical trial comparing the efficacy and safety of ixekizumab (IXE) versus) to adalimumab (ADA), the percentage of patients simultaneously achieving American College of Rheumatology 50 (ACR50) and Psoriasis Area and Severity Index 100 (PASI100), was the primary endpoint in order to reflect improvement in two domains of PsA. Objectives: To evaluate how individual components of the simultaneous achievement of ACR50 and PASI100 compare with those of MDA at week 24. Methods: Patients with active PsA (defined as those with a tender joint count [TJC] ≥ 3/68, a swollen joint count [SJC] ≥ 3/66 and a body surface area [BSA] of active plaque psoriasis ≥ 3%) were randomised 1:1 to approved dosing (according to baseline psoriasis involvement) of IXE or ADA in SPIRIT-H2H, an open label, assessor-blinded study. The proportion of patients meeting each criterion of the composite endpoints was calculated for the intent-to-treat ([ITT], N=566) population and the population of MDA responders at Week 24 (N=235). Missing individual responses were imputed with non-responder status. Spidergrams were generated using SAS 9.4. Results: For both the overall ITT population and the MDA responders population, the use of PASI≤1 or BSA≤3% in the skin-related component of the MDA contributed to the higher response rate relative to the PASI100 response. Thus, the PASI100 response is a more stringent endpoint. Proportions of responders are similar across MDA and ACR50+PASI100 individual components for HAQ and SJC. The high baseline TJC levels (mean TJC: IXE=19.1, ADA=21.3) as opposed to lower levels observed for baseline SJC (mean SJC: IXE=10.1, ADA=10.7) made MDA-TJC criterion (≤1) more difficult to achieve than the equivalent criterion of the ACR50+PASI100 endpoint. Conclusion: Despite the differences in criteria definitions, there are consistent response patterns in the individual components of the simultaneous ACR50+PASI100 and MDA endpoints in particular for the peripheral arthritis domain. References: [1]Smolen, Josef S et al. "Treating axial spondyloarthritis and peripheral spondyloarthritis, especially psoriatic arthritis, to target: 2017 update of recommendations by an international task force." Annals of the rheumatic diseases vol. 77, 1 (2018): 3-17. [2]Mease PJ The SPIRIT H2H study group, et al . "A head-to-head comparison of the efficacy and safety of ixekizumab and adalimumab in biological-naïve patients with active psoriatic arthritis: 24-week results of a randomised, open-label, blinded-assessor trial." Annals of the Rheumatic Diseases 2020;79: 123-131. Disclosure of Interests: Laura C Coates: None declared, Michael Nissen Grant/research support from: Abbvie, Consultant of: Novartis, Lilly, Abbvie, Celgene and Pfizer, Speakers bureau: Novartis, Lilly, Abbvie, Celgene and Pfizer, Celine El Baou Consultant of: Eli Lilly and Company, Jane Zochling Employee of: Jannssen Cilag, Speakers bureau: Janssen Cilag, AbbVie, Novartis, UCB, BMS, Eli Lilly, Antonio Marchesoni Speakers bureau: Abbvie, Pfizer, UCB, Novartis, Celgene, Eli Lilly, Soyi Liu Leage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Enrique Soriano Grant/research support from: AbbVie, Eli Lilly, GlaxoSmithKline, Novartis, Pfizer Inc, Sandoz, Consultant of: AbbVie, Eli Lilly, GlaxoSmithKline, Novartis, Pfizer Inc, Sandoz, Speakers bureau: AbbVie, Amber, Bristol-Myers Squibb, Eli Lilly, Novartis, Pfizer Inc, Roche, Valderilio F Azevedo Grant/research support from: Abbvie, Janssen, Bristol-Myers Squibb, Boehringer-Ingelheim, Lilly and Novartis, Consultant of: Lilly, Novartis, Janssen, Boehringer-Ingelheim, Amgen, Pfizer and Abbvie, Speakers bureau: Sandoz, Celltrion, Lilly, Novartis, Janssen, Boehringer-Ingelheim, Amgen, Pfizer and Abbvie, Klaus Machold Grant/research support from: AbbVie, MSD, UCB, Consultant of: Arsanis, Astro, Baxter, BMS, Celgene, Eli-Lilly, MSD, Pfizer, Roche, Novartis, Sandoz, Speakers bureau: MSD, Pfizer, BMS, Janssen-Cilag, Sandoz, Novartis, Eli-Lilly, Christophe Sapin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company